2019
DOI: 10.2147/cmar.s189052
|View full text |Cite
|
Sign up to set email alerts
|

<p>The role of long non-coding RNA GAS5 in cancers</p>

Abstract: Long non-coding RNAs (lncRNAs) have shown potential as a biomarker in the diagnosis and prognosis in multiple cancers. LncRNAs are dysregulated in various cancers, playing either oncogenic or tumor suppressive roles. Emerging evidences have proved that the growth arrest-specific 5 ( GAS5 ) lncRNA can function as a tumor suppressor in several cancers. LncRNA GAS5 is downregulated in many types of cancer, regulating cellular processes such as cell proliferation, apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 80 publications
3
48
0
Order By: Relevance
“…Recently, increasing evidence indicated that decreasing expression of GAS5 can affect the susceptibility of many kinds of cancers and associated with poorer prognosis of hepatocellular carcinoma, cervical cancer, renal cancer, lung cancer, gastric cancer and melanoma [24][25][26][30][31][32]. The rs145204276 ins/del polymorphism can regulate the expression of GAS5 through affecting one CpG island methylation condition [24].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, increasing evidence indicated that decreasing expression of GAS5 can affect the susceptibility of many kinds of cancers and associated with poorer prognosis of hepatocellular carcinoma, cervical cancer, renal cancer, lung cancer, gastric cancer and melanoma [24][25][26][30][31][32]. The rs145204276 ins/del polymorphism can regulate the expression of GAS5 through affecting one CpG island methylation condition [24].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these results reveal that GAS5 is an important regulator of propofolinduced OSCC cell apoptosis increase and cell proliferation decrease. GAS5 acts as a ceRNA of miR-1297 and downregulates miR-1297 expression upon propofol treatment GAS5 can act as a competing endogenous RNA (ceRNA) to regulate tumourigenesis [14]. A recent study indicated that GAS5 sponges miR-205 and suppresses miR-205 expression [18].…”
Section: Lncrna Gas5 Induced By Propofol Inhibits Cell Growth and Promentioning
confidence: 99%
“…Growth arrest-specific 5 (GAS5) can encode ncRNAs of various sizes, including lncRNAs [13]. Emerging evidence has proven that lncRNA GAS5 is an important tumour suppressor that is downregulated in many types of cancers and involved in many cellular processes, such as cell proliferation, apoptosis and invasion [14]. Although GAS5 has been indicated to play an important role in cancer, the functions of GAS5 in response to propofol treatment are not well studied.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, translation initiation (EIF1A, EIF4A, EIF4G) and elongation (EEF1B2, EEF2) factors are well-known to play a role in cancer [35,36], as well as ribosome biogenesis related factors, like the pseudouridine synthase dyskerin [37] and the 2 -O-methyltransferase fibrillarin [38]. In addition, non-coding host genes have recently been found to be involved in cancer onset or progression, for example ZFAS1 [39], GAS5 [40], and MEG8 [41]. On top of these, multiple host genes are known regulators of cell metabolism, cell cycle, cell adhesion, and cell signaling, and their de-regulation therefore may be involved in cancer development.…”
Section: Discussionmentioning
confidence: 99%